Opportunity cost of environmental preservation: the case of the Brazilian Legal Amazon - Andre Chagas; Luiza Andrade (European Regional Science Association (ERSA), 2013)
Currently, the region named Brazilian Legal Amazon (BLA) represents the agricultural frontier of Brazil, and it concentrates the deforestation processes, so-called arc of deforestation. This region covers the total area of Acre, Amapá, Amazonas, Pará, Rondônia, Roraima, and Tocantins, and part of Mato Grosso and Maranh\~ao states. A recurrent discussion involves what to do to reducing deforestation process. A compensation to no-deforestation is a way to this. This work estimated the opportunity cost involved in preserving the local forest by private agents in the Brazilian Legal Amazon (BLA), an important consideration for planned compensation program. In general, the traditional approach considers only the current local earnings to estimate this compensation. But, the no-deforestation option implies to the agent an opportunity cost, represented by expected cash flow that these agents lose by not using the land for agricultural production in the future. In this case, a compensation program should consider the lost future income. The formation expectation process is uncertain, but the occupation in Brazil?s Midwest, a region near to BLA, in the seventies and eighties, can provide a proxy. The Midwest was region of more intensive agricultural growth in last forty years in Brazil. So, the agents in BLA can compare the actual development stage, in their region, with to the Midwest, forty years ago. In other words, BLA production would be at a similar stage to Midwest in early seventies, and the BLA's producers would expect to similar performance to the Midwest in the next years. We use the stochastic frontiers method, with land, labor, and capital as inputs, and real agricultural production as output, to compare both regions and conclude that the actual production mode in BLA is really very similar to the Midwest, in the past. So, we take the production function estimate to the Midwest, for the 1970 to 2006 periods as a proxy to the production in BLA, conditioned to BLA's characteristics, and we estimated the future income flow for this region. This is the same that assume a maximum expected profitability for BLA production. The results show that the producers in the BLA region would expect a 9% to 13% increase in average annual income for the next forty years, depending on the discount rate of the cash flow.
Keywords: Q15; Q56; H2; R11; 330; Brazilian Amazon Legal; deforestation; environmental compensation; forest valuation